Educational Revitalization of the Children with Special Needs at an Inclusive School - Adhi, Made Kerta; Seniwati, Ni Putu (Jurnal Ilmiah Peuradeun, 2018)
The main purpose of this research is to find out the forms and meaning of revitalization of children with special needs at an inclusive school, particularly at Saraswati Elementary School, Tabanan, and Bali. This research is a qualitative research with an approach of a Cultural Study. The results show that the forms of revitalization are increasing resources, such as the workshop of teachers and students parents; providing apprentice for school staff, especially the manager of school library; increasing the involvement of children with special needs with the other common peers in self-development; equipping facilities such as special guidance room and library facilities. The meaning of revitalization is to improve the quality of human resources, togetherness in differences, and the development of potential children with special needs. In conclusion, there are enhancement of knowledge, skills, and behavior of teachers and educational staff respectively with the average of 88 and 90 percent, parents become more empathetic to the children, and social cohesion between children with special needs and normal children is established, so children with special needs are able to grow well.